Laurillard, D. (2012). Teaching as a Design Science. Building pedagogical patterns for learning and technology. New Yorl & London: Routledge. 258 págs. - Bower, Matt (Revista Fuentes, 2018)
In short time Teaching as a Design Science by Diana Laurillard has become a spearhead for the recent and growing field of Learning Design. The articulate and convincing argument for treating teaching as a design science has provided educators worldwide with a new frame of reference for thinking about their practice.